A Factorial Analysis Study On Factors Contribution To Ferulic Acid Production From Oil Palm Frond Waste - Zulsyazwan, Ahmad Khushairi; Hafizuddin, Wan Yussof; Nurul Atikah, Rodzri; Rozaimi, Abu Samah; N., Zainol (Penerbit Universiti Teknologi Malaysia, 2016)
Enzymatic hydrolysis of fibre-pressed oil palm frond (FPOPF) was done using mix culture for the production of ferulic acid. Mix culture was prepared by acclimatizing the soil obtained from palm oil plantation with FPOPF substrate for 30 days. The substrate had a ratio of FPOPF to water of 1:10. Design Expert 7.1 was used to aid the experimental design. A half fractional two-level factorial analysis with five factors was selected for the experimental design resulting in a total of 16 runs. The factors controlled were temperature (A; 26°C and 40°C), pH value (B; 5 and 9), agitation speed (C; 0 and 150 rpm), inoculum percentage (D; 2% and 10%), and response time (E; 1 and 3 days). The result obtained showed that the experimental design model was significant with a coefficient of determination value of 0.8978. Two factors that contributed the most to the process were temperature and pH value. This model was proved to be repeatable with a validation test percentage error at 4.15% to 6.83%.